Accelerated urban sprawl in Montreal, Quebec City, and Zurich: Investigating the differences using time series 1951–2011. (January 2016) - Nazarnia, Naghmeh; Schwick, Christian; Jaeger, Jochen A.G.
Graphical abstract: Highlights: Urban sprawl has increased exponentially in Montreal since 1951. In Montreal and Quebec City, urban sprawl is now increasing faster than ever before. Quebec City is a prime example of urban sprawl today. Sprawl was higher in Zurich before 1980, then was surpassed by Montreal and Quebec City. Reasons are stronger planning legislation and better public transportation in Switzerland. Abstract: Increasing awareness of the negative effects of urban sprawl has made sprawl a topic of great debate. However, higher efforts are needed to protect forests, agricultural lands, and other open spaces from urban sprawl. This study compares patterns of accelerated increase in sprawl in the Montreal and Quebec Census Metropolitan Areas in Canada with the Zurich metropolitan area in Switzerland between 1951 and 2011. We applied the recent metrics of urban permeation ( UP ) and weighted urban proliferation ( WUP ) to measure urban sprawl. Urban sprawl has accelerated continuously in Montreal and Quebec since 1951. Here, the fastest increases in sprawl have been observed in the last 25 years, whereas in Zurich the strongest acceleration was in the 1960s. Urban sprawl has increased exponentially in Montreal since 1951. On the Island of Montreal, the degree of urban sprawl ( WUP ) increased 26-fold from 0.49 UPU/m 2 in 1971 to 12.74 UPU/m 2 in 2011, while in Quebec City it increased 9-fold from 2.41 UPU/m 2 to 21.02 UPU/m 2 from 1971 to 2011. In contrast, the level of sprawl ( WUP ) in the Inner Zurich metropolitan area increased almost 3-fold from 3.12 UPU/m 2 in 1960 to 8.91 UPU/m 2 in 2010, i.e., it was higher before 1980, but then was surpassed by Montreal and Quebec City. The strongest increases in land uptake per person were observed in Quebec City and on the Island of Montreal, while it increased only slightly in Zurich. Two major reasons for this striking difference in sprawl dynamics are Switzerland's stronger planning legislation since 1979 and a much higher level of public transportation availability in Zurich. The comparative analysis of urban sprawl presented in this study can greatly help land-use planners critically assess projected plans and control urban sprawl and its negative consequences. The WUP method can also be used to establish targets and limits to urban sprawl and to evaluate the effectiveness of measures to control sprawl.